Integration of Digital Systems and Sitorem Method for Strengthening Science Management - Iman Indrati; Henny Suharyati; Dian Wulandari (Jurnal Penelitian Pendidikan IPA, 2025)
Effective knowledge management (KM) is pivotal for higher education institutions to maintain competitiveness. This study aims to formulate a targeted strategy for enhancing lecturer KM by identifying critical indicators requiring immediate intervention, based on SITOREM analysis. The research is grounded in the theory of organizational knowledge creation, hypothesizing that a focused improvement on pivotal KM processes and supporting factors will lead to a more effective and sustainable KM system. This quantitative research employed a survey method to collect data from lecturers at a higher education institution. Data were analyzed using the SITOREM method to identify strengths, weaknesses, and key improvement priorities within the KM framework, focusing on the five fundamental KM processes: acquisition, refinement, storage, dissemination, and application. The analysis revealed that knowledge evaluation is an institutional strength to be maintained. However, critical weaknesses were identified in knowledge acquisition and application processes. Supporting factors such as organizational rewards and educator development are potential levers, while challenges persist in team collaboration, leadership empathy, and information technology security and ethics. These findings align with prior research emphasizing that technological infrastructure and a collaborative culture are prerequisites for successful KM implementation, directly impacting the cycle of organizational learning. The study concludes that an optimal KM enhancement strategy requires an integrated approach, simultaneously improving critical KM processes, strengthening collaborative culture, enhancing leadership social skills, and ensuring digital ethics, thereby creating a systematic and sustainable KM system.